2005
DOI: 10.1901/jaba.2005.176-03
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Reinforcement Control Procedures

Abstract: A demonstration of the effects of reinforcement requires comparison of response rates in the presence of a contingency with those in another condition that controls for the influence of extraneous variables. We describe several control conditions that have been used in evaluating the effects of positive and negative reinforcement. The methodological rigor and practical utility of each type of control condition are discussed, and recommendations for the use of these conditions are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 74 publications
1
49
0
9
Order By: Relevance
“…In order to ensure that frequency of caregiver vocalizations could not account for differences in infant vocalizations between sessions, the audiotape was used to yoke the number of vocalizations from the contingent imitation condition to the control condition. A DRO schedule was utilized to prevent reinforcement of infant vocalizations during the control condition while still providing some form of reinforcement for other emitted behavior; prior research has demonstrated this to be an effective control procedure in place of extinction-based control conditions that would likely evoke emotional responding in young children (Poulson 1983;Thompson and Iwata 2005).…”
Section: Methodsmentioning
confidence: 99%
“…In order to ensure that frequency of caregiver vocalizations could not account for differences in infant vocalizations between sessions, the audiotape was used to yoke the number of vocalizations from the contingent imitation condition to the control condition. A DRO schedule was utilized to prevent reinforcement of infant vocalizations during the control condition while still providing some form of reinforcement for other emitted behavior; prior research has demonstrated this to be an effective control procedure in place of extinction-based control conditions that would likely evoke emotional responding in young children (Poulson 1983;Thompson and Iwata 2005).…”
Section: Methodsmentioning
confidence: 99%
“…A condição ideal para avaliar os efeitos de uma contingência é comparando condições nas quais essa contingência está presente com aquelas nas quais a contingência está ausente (Catania & Keller, 1981;Thompson & Iwata, 2005). Por essa razão, dois procedimentos de suspensão da metacontingência foram avaliados: a suspensão da apresentação do evento cultural e apresentação desse evento de forma independente do desempenho dos participantes.…”
Section: Critérios De Mudança De Condiçãounclassified
“…Um dos procedimentos de controle mais largamente utilizados é a extinção padrão, na qual se suspende a apresentação de um estímulo previamente estabelecido como reforçador de uma resposta 2005;Thompson, Iwata, Hanley, Dozier & Samaha, 2003). A aplicação desse procedimento tem gerado sistemática redução na taxa de respostas previamente reforçadas, evidenciando o poder do evento reforçador no controle do comportamento (Lerman & Iwata, 1996; 2005; Thompson et al, 2003 ).…”
unclassified
See 2 more Smart Citations